Would a hypothetical merger between Peru’s two largest newspaper conglomerates have been cleared? A two-sided multi-media analysis - Defilippi, Enzo (2018)
This study uses an original data set on the Peruvian media sectors to analyze the effect that the association between the two largest newspaper conglomerates would have on the content and advertising markets. This case is particularly relevant given the particularities of Peru’s competition framework and media markets. Using survey data, we conclude that Peruvian newspapers face effective competition from other media sectors in both the content and advertising markets. Our analysis shows that both markets are “unconcentrated” according to the U.S. Horizontal Merger Guidelines and thus, the operation would be cleared. However, if concentration is analyzed taking into account only news-providing media and programs, the market would be categorized as “moderately concentrated” and a full merger between these conglomerates would warrant further scrutiny.